Oyster Mushroom in Bioremediation: A Review of Its Potential and Applications - Moses, Iyekekpolor Osamudiame (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Oyster mushrooms (Pleurotus spp.), a widely cultivated edible fungus, hold immense potential in the field of bioremediation due to their unique physiological and enzymatic capabilities. Bioremediation is an eco-friendly process that employs biological systems to degrade, immobilize, or transform environmental pollutants, such as heavy metals, polycyclic aromatic hydrocarbons (PAHs), pesticides, and synthetic dyes, into less toxic or reusable forms. Oyster mushrooms stand out due to their ability to grow on diverse substrates, rapid growth rates, and secretion of ligninolytic enzymes, such as laccases and manganese peroxidases, which break down complex pollutants. Additionally, their mycelial networks exhibit biosorption properties that effectively bind and immobilize heavy metals, making them ideal candidates for mycoremediation. This review explores the mechanisms underlying the bioremediation capabilities of oyster mushrooms, focusing on enzymatic degradation of organic pollutants and biosorption of heavy metals. Furthermore, the economic and environmental advantages of using oyster mushrooms in bioremediation are discussed, including cost-effectiveness, dual benefits of waste recycling and edible mushroom production, and adaptability to various environmental conditions. The paper also highlights challenges such as enzyme specificity, scalability, and secondary metabolite toxicity. Future research directions include genetic engineering to enhance enzymatic efficiency, co-cultivation strategies with other microorganisms, and field trials to validate laboratory findings. Oyster mushrooms thus represent a sustainable, versatile, and efficient approach to addressing global pollution challenges.